Hurst's the heart - Hurst, John Willis, 1945-; Fuster, Valentin; Walsh, Richard A., 1946-; Harrington, Robert A. (New York : McGraw-Hill Medical, 2011)
The trusted landmark cardiology resource thoroughly updated to reflect the latest clinical perspectives Includes DVD with image bank Through thirteen editions Hursts the Heart has always represented the cornerstone of current scholarship in the discipline. Cardiologists, cardiology fellows and internists from across the globe have relied on its unmatched authority breadth of coverage and clinical relevance to help optimize patient outcomes. The thirteenth edition of Hursts the Heart continues this standard-setting tradition with 19 new chapters and 59 new authors, each of whom are internationally recognized as experts in their respective content areas. Featuring an enhanced reader-friendly design the new edition covers need-to-know clinical advances as well as issues that are becoming increasingly vital to cardiologists worldwide. As in previous editions you will find the most complete overview of cardiology topics available plus a timely new focus on evidence-based medicine health outcomes and health quality. New Features: 1548 full-color illustrations and 578 tables. Companion DVD with image bank includes key figures and tables from the text.
The Cardiovascular Disease: Past, Present, and Future section includes a new chapter on assessing and improving quality of care in cardiovascular medicine. The section on the scientific foundations of cardiovascular medicine has been thoroughly revised. 2 new chapters in the section on the evaluation of the patient detail the process of effective diagnostic decision making based on technology, clinical trials, and practice guidelines. A new chapter in the section on heart failure details cardiac transplantation. The sections on primary heart disease include new chapters on topics such as preventive strategies for coronary artery disease and updated pharmacologic strategies for acute coronary syndromes. The section on cardiopulmonary disease features new chapters on chronic cor pulmonale and sleep disorder breathing and its relationship to cardiovascular disease. The section on valvular heart disease has four of the six chapter completely rewritten by new authors who are authorities in the fieldThe final six sections feature new chapters on the environment and heart disease, surgical treatment of carotid and peripheral vascular disease and cost effective strategies in cardiology--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cardiovascular system -- Diseases; Heart -- Diseases; Cardiovascular Diseases